INFLUENCE OF EXTREMELY HIGH FREQUENCY ELECTROMAGNETIC RADIATION ON THE STRESSOR ULCEROGENESIS - Ravaeva, M.Yu.; Chuyan, E.N.; Beregovaya, T.V. (World of Medicine and Biology, 2013)
It is shown that electromagnetic radiation of extremely high frequency limits the formation of all kinds of destructions ulcerative gastric mucosa and limit the development of the stress response in the forced swimming test.